QUA VADIS PEMBERLAKUAN PKPU NOMOR 7 TAHUN 2015 DAN PKPU NOMOR 5 TAHUN 2015 TERHADAP PARTISIPASI PEMILIH MASYARAKAT DALAM PILKADA 2015 DI PROVINSI BALI - Widhiasthini, Ni Wayan (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
Changes to the substance of the legislation are followed the regulatory changes in the underlying consequences. Likewise, changes election law, which gave birth to more technical arrangement of elections in 2015, especially on the campaign Unison. Efforts pairs of candidates in the campaign for voters was allegedly bound by very strict rules. On the other side of the KPU as election organizers also sought over resources and efforts through socialization, voter education and to increase voter participation. Hopes implementation of elections Unison 2015 to realize realize the election of regional heads who have the competence, integrity and capability as well as meet the elements of acceptability has not been followed by public participation optimally.